2022
DOI: 10.1002/14651858.cd009353.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Crisis interventions for adults with borderline personality disorder

Abstract: Analysis 1.2. Comparison 1: Joint crisis plan (JCP) plus treatment as usual (TAU) versus TAU alone, Outcome 2: Death: number of deaths during study period (worst-case scenario; sensitivity analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…So far, however, such interventions have not been shown to decrease the amount of inpatient care, self-harm episodes, suicide attempts, deaths, or compulsory care. 71,72 On the other hand, patients have felt validated and content with such interventions. 73,74…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, however, such interventions have not been shown to decrease the amount of inpatient care, self-harm episodes, suicide attempts, deaths, or compulsory care. 71,72 On the other hand, patients have felt validated and content with such interventions. 73,74…”
Section: Discussionmentioning
confidence: 99%
“…Advance statements, joint crisis plans, and self-referred brief admissions are all interventions that have been tried for patients with BPD. [71][72][73][74] Theoretically, these measures may sound palatable, since they intend to increase the patient's agency, increase therapeutical alliance, decrease self-harm behaviour, and decrease the need for compulsory care. So far, however, such interventions have not been shown to decrease the amount of inpatient care, self-harm episodes, suicide attempts, deaths, or compulsory care.…”
Section: Resistance To Changementioning
confidence: 99%
See 1 more Smart Citation
“…The literature for acute care is smaller than for community care for people with this diagnosis, which is also under researched [ 67 ]. The review included studies that were found in the previous more focused reviews [ 10 , 12 ], but also included a wider range of literature.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews examining crisis interventions and services for people with a ‘personality disorder’ diagnosis have limited inclusion criteria to randomised controlled trials (RCTs) or have not included studies reporting outcomes from commonly used crisis service models. A Cochrane review performed in 2022 of crisis interventions designed for people with a ‘personality disorder’ diagnosis found only two studies: a RCT of a brief admission intervention [ 9 ] and a pilot RCT of crisis planning [ 10 , 11 ], both reporting no effect of the study intervention compared to treatment as usual. A systematic review conducted in May 2022 searched for randomised and observational studies of crisis-focused psychosocial interventions for ‘borderline personality disorder’ that can be delivered within acute care and found five studies [ 12 ].…”
Section: Introductionmentioning
confidence: 99%